2012
DOI: 10.1136/gutjnl-2011-300971
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic and postbiotic activity in health and disease: comparison on a novel polarised ex-vivo organ culture model

Abstract: Background and aims Probiotics and their metabolic products, here called postbiotics, have been proposed as food supplements for a healthier intestinal homeostasis, but also as therapeutic aids in inflammatory bowel disease (IBD) with, however, very little clinical benefit. This may be due to the lack of reliable preclinical models for testing the efficacy of different strains. Methods The activity of three probiotic strains of Lactobacillus (or a postbiotic) was analysed and compared with a pathogenic strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(257 citation statements)
references
References 27 publications
5
234
0
8
Order By: Relevance
“…[4][5][6] When either FITC-dextran species was added to the luminal media they passed through the tissue within 25 min (data not shown). Biopsies from five independent patients were studied, and no obvious differences were observed in perfusion kinetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] When either FITC-dextran species was added to the luminal media they passed through the tissue within 25 min (data not shown). Biopsies from five independent patients were studied, and no obvious differences were observed in perfusion kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…This local reaction leads to an increased influx of intestinal material into the cell wall creating an inflammatory response within the gut. [4][5][6] IBD is a chronic disease without medical cure and requires lifetime care with a possibility of surgery, as well as the increased risk of colorectal cancer. [7][8][9][10] Current research models into IBD either require inducing the disease in murine models or using cell culture, both which fail to fully replicate the extent of the disease seen in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Mileti et al (37) found that Lactobacillus paracasei displayed a delay in the development of colitis and a decreased severity of disease but that L. plantarum and L. rhamnosus GG exacerbated the development of dextran sodium sulfate (DSS)-induced colitis. In contrast, Tsilingiri et al (39) found that L. plantarum induced an inflammatory response in the healthy tissue cultured ex vivo at the end of incubation that resembled the response induced by Salmonella. Moreover, L. paracasei, L. plantarum, and L. rhamnosus GG were detrimental in the inflamed tissue derived from IBD patients cultured ex vivo, whereas the supernatant from the culture system of L. paracasei directly acted on the tissue and downregulated the proinflammatory activities of the existing leukocytes (39).…”
Section: Discussionmentioning
confidence: 96%
“…Numerous model systems exist to study the links between gut microbiota and host metabolism, including in vitro cell culture models [4], in vitro gut models [5], ex vivo organ models [6], animal models [7 ,8 ], human in patient studies [9], and cohort studies (e.g. [10,11]).…”
Section: Types Of Host-microbe Interactionsmentioning
confidence: 99%